2018
DOI: 10.1103/physrevb.98.045429
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-phonon coupling in a valley-spin-polarized two-dimensional electron system: A theoretical study on monolayer silicene

Abstract: We study the hybrid excitations due to the coupling between surface optical phonons of a polar insulator substrate and plasmons in the valley-spin-polarized metal phase of silicene under an exchange field. We perform the calculations within the generalized random-phase approximation where the plasmon-phonon coupling is taken into account by the long-range Fröhlich interaction. Our investigation on two hybridized plasmon branches in different spin and valley subbands shows distinct behavior compared to the unco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In addition, the electrostatic potential gradient between WSe 2 and CrI 3 should also play a role in lifting the valley degeneracy. Previous studies demonstrated that applying a vertical external electric field combining with a magnetic field can significantly increase the valley splitting in silicene [8][9][10]12,14 . Similar effects might be at function here in the WSe 2 /CrI 3 , where a vertical electric field is generated from an interlayer electrostatic potential gradient as shown in Fig.…”
Section: A Geometric Structure Of Wse2/cri3mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the electrostatic potential gradient between WSe 2 and CrI 3 should also play a role in lifting the valley degeneracy. Previous studies demonstrated that applying a vertical external electric field combining with a magnetic field can significantly increase the valley splitting in silicene [8][9][10]12,14 . Similar effects might be at function here in the WSe 2 /CrI 3 , where a vertical electric field is generated from an interlayer electrostatic potential gradient as shown in Fig.…”
Section: A Geometric Structure Of Wse2/cri3mentioning
confidence: 99%
“…It is crucial to achieve large valley polarization, in analogous to large spin polarization in spintronics, for the development of valleytronics devices. A plenty of exotic properties such as quantum spin/valley anomalous Hall effect [8][9][10] , valleydependent optoelectronics 11 , spin/valley polarization of plasmons [12][13][14] , magneto-optical conductivity 15 , electrical transport of valley carriers 16 have been explored in the valley-polarized systems. Moreover, valley polarization may interplay with spin polarization, especially to enhance spin polarization 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…1. The thickness considering the vdW distance of germanene (4.889 Å) 46 is greater than that of silicene (4.650 Å), 47 which may be due to its larger relative atomic mass and radius. The lattice constants of the three materials increase exponentially with increasing electric field strength in the z direction (perpendicular to the plane).…”
Section: Resultsmentioning
confidence: 97%
“…50,51 Particularly, we are interested in the valley-spin polarized metal (VSPM) phase of silicene due to its rich underlying valley and spin physics. 24,52 We show that both the real and imaginary parts of silicene self-energy depend upon the spin and valley degrees of freedom where the change in the imaginary part is more pronounced. Moreover, we obtain the single-particle spectral function of carriers for four different states (four distinct combinations of the spin and valley indexes).…”
Section: Introductionmentioning
confidence: 87%